The parasite Monascus filiformis (Trematoda, Digenea, Fellodistomidae) on Stromateus brasiliensis (Pisces, Perciformes, Stromateidae): Possible routes of transmission involving jellyfish - Diaz Briz, Luciana Mabel (2016)
A new final fish host (Stromateus brasiliensis) for the digenean parasite Monascus filiformis from the continental shelf of Patagonia Argentina in the South-western Atlantic Ocean is reported. This demersal-pelagic fish (commonly denominated pampanito) is exclusively a jellyfish consumer. It is well known that larval stages of Monascus filiformis mostly use medusae as secondary hosts. Therefore, the pampanito likely acquires this parasite when it predates upon some species of parasitized medusae in the area. This work improves the knowledge about the final hosts of this parasite and infers which species of medusa may be involved in their life cycle.